Self-assembled polyaniline nanostructures in situ deposited on silica optical fibers for ammonia gas sensing - Ibrahim, Siti Azlida; Abdul Rahman, Norizah; Yaacob, Mohd Hanif; Abu Bakar, Muhammad Hafiz; Mohamad, Fatimah Syahidah; Mohd Yahya, Nor Akmar; Md. Yusoff, Nelidya; Mahdi, Mohd Adzir (Elsevier, 2022)
Optical fibers coated with polyaniline (PANI) nanostructures were used to sense ammonia gas (NH3) concentration. The PANI nanostructures were synthesized using the oxidative polymerization process in a solution containing poly(methyl vinyl ether-alt-maleic acid) (PMVEA). The PANI nanostructures were in situ deposited on silica optical fibers by immersing the fibers in the solution during the polymerization process for specific durations. The morphology and the thickness of the PANI nanostructure coatings were characterized using Scanning Electron Microscopy (SEM). Raman and Fourier Transform Infra-red (FTIR) spectra confirmed that the PANI nanostructures were in the emeraldine salt (ES) state. The sensors were exposed to various concentrations of NH3 gas at room temperature. The sensor with a coating thickness of 639 nm shows the highest response with a cumulative absorbance response of 2.2 towards 1% NH3 in synthetic air. The response and recovery times are 2.82 min and 11.52 min, respectively.